The Peran Employee Engagement sebagai Variabel Mediasi: Pengaruh Pendidikan dan Pelatihan (Diklat) dan Employer Branding terhadap Kinerja Karyawan - Adylia Disca; Eko Wahjudi; Dewie Tri Wijayati Wardoyo; Riedel Paulus Jacobis (Jurnal Ilmu Manajemen, 2026)
This study was motivated by a decline in employee productivity, reflected in a drop in revenue per full-time equivalent (FTE) from USD 1.62 million in 2023 to USD 1.44 million in 2024, alongside an increase in employee costs per FTE from USD 176,000 to USD 212,000. Consequently, this study analyzes the mediating role of employee engagement in the relationship between education and training programs, employer branding, and employee performance within an oil and gas company. A quantitative approach was employed, utilizing primary data collected through observation, interviews, and questionnaires distributed to 89 employees of the oil and gas company. The variables examined included education and training, employer branding, employee engagement, and employee performance; hypotheses were tested using the SEM-PLS method with SmartPLS 4.0 software. The findings indicate that education and training, employer branding, and employee engagement all have a positive effect on employee performance; furthermore, education and training and employer branding positively influence employee engagement. The study also reveals that employee engagement positively and significantly mediates the impact of education and training and employer branding on employee performance. These results suggest that enhancing employee performance within the company depends not only on competency development and corporate image but also on the extent to which these factors translate into psychological attachment and work dedication among employees.